KEBIJAKAN LITERASI DIGITAL DOSEN DALAM MEMBANGUN ETIKA KOMUNIKASI AKADEMIK DI PERGURUAN TINGGI - Iranda Hari Fadhil, Hasan Sazali (LP2M Universitas Muslim Nusantara Al Washliyah, 2026)
This study aims to examine the role of lecturers in developing students' digital literacy, developing media ethics, fostering a culture of healthy scientific discussion in the digital space, and increasing students' regulatory awareness of the responsible use of digital media. The study employed a qualitative approach with library research methods and a conceptual case study perspective. Data were obtained from scientific journals, books, international agency reports, and policy documents relevant to digital literacy, academic communication ethics, and higher education. Data analysis was conducted through content analysis and thematic analysis to identify key themes emerging in the literature. The study results indicate that lecturers play a role as communicators, facilitators, moderators, educators, and normative agents in shaping students' digital literacy. Lecturers contribute to improving critical thinking skills regarding digital information, instilling ethical media values, developing a culture of scientific discussion based on rational argumentation and data, and raising students' awareness of regulations related to copyright, academic integrity, personal data protection, cybersecurity, and the use of artificial intelligence. The integration of these four aspects is a crucial foundation for building a productive, ethical, and sustainable digital academic communication ecosystem in higher education.